Factores familiares y su relación con factores de riesgo modificables para hipertensión en adultos de 20 a 64 años Loja 2016. - Poma Minga, Jorge Luis (2017)
Family health is linked to the effective functioning of it. Individual health is developed in the context of a family with the formation of: Habits, lifestyles, value systems, norms, attitudes and behaviors towards health. On the other hand, hypertension is a process of high prevalence and one of the main preventable causes of cardiovascular complications. Some associated risk factors can be prevented. The present cross-sectional, correlational study of 414 participants was proposed as a general objective to determine the function and family crisis; and, its relation with adjustable risk factors for hypertension in adults aged 20 to 64 years of the city of Loja. The analysis of this relationship contributes to the advancement of knowledge and as a basis for delineating preventive strategies. The correlation between these variables shows that family dysfunction is a risk factor for presenting: Low level of physical activity OR 1.61 (CI95% = 1.03 - 2.52); tobacco consumption OR 1.63 (CI95% = 1.04 - 2.55); overweight-obesity OR 1.77 (CI95% = 1.13 - 2.76); altered blood pressure OR 2.00 (CI95% = 1.22 - 3.28); consumption of alcohol at risk OR 5.69 (CI95% = 3.59 - 9.01). Family crises were a risk factor in the development of: overweight-obesity OR 2.60 (CI95% = 1.62 - 4.17) and alcohol consumption risk OR 1.84 (CI95% = 1.13 - 3.00). The data obtained establish that: dysfunction and family crisis are a predisposing factor in the development of behaviors and adjustable hypertension risk factors. Key Words: Family medicine, risk factors, body mass index, tobacco use, obesity.